The Role of HR Practices in Enhancing Firm Supply Chain Performance - Sinaga, Obsatar; Nurfarina, Anne; Iskandar, Asep Deni; Mozammel, Soleman; Rosita, Ai (International Journal of Supply Chain Management, 2019)
The supply chain management is an emerging discipline, which during the course of three decades has emerged from an operational function to a competitive strategy. The authors have employed different theoretical models to explain the success factors of supply chain management. The current study is carried out to explain the relationship between HR practices and supply chain performance. In addition to that the current study, is also interested in finding the impact of organizational culture in the relationship between a set of HR practices and supply chain performance. To achieve the research objectives, we have employed two step smart PLS technique, which is one of the robust SEM technique of recent times. We have used the smart PLS as statistical tool to achieve the research objectives the data by mean of an adapted survey instrument in the form of questionnaire is collectedfrom the operation and finance managers of Indonesian manufacturing firms. The results of the current study are providing support to the hypothesized results. The direct and indirect relations appear positive and significant. The current study which in author knowledge is among few pioneering studies on this issue, will be helpful for financial experts, operation managers, academicians, researchers and other policy makers in formulating policies.